The Impact of Economic Uncertainty on Food Security and the Role of Business Openness as a Moderating Factor in Indonesia's Economic Development - Sahetapy, Willyan (International Journal of Management Science and Information Technology, 2025)
The economic uncertainty experienced by developing countries like Indonesia has the potential to disrupt food security, which is an essential element for social and economic stability. Changes in the international economic environment, such as inflation, fluctuation in exchange rates, and variations in international policies can often have an impact on supply or availability of food. But it is under these circumstances that business openness must function as an instrument of moderation in increasing uncertainty for food security. As a result, this research attempts to discuss the relationship between economic uncertainty and food security in Indonesia, and how business openness serves to amplify or dampen the effects of economic uncertainty on food production. Panel data from the years 2019 to 2024 is used cm this analysis. The findings bring out that business openness has a positive effect on food security, while economic uncertainty has a negative one. Meanwhile, interaction between economic uncertainty and business openness suggests that the more open an economy is economically, the less negative will be its weight on food production. It underscores the importance of policies combining good with global integration to the domestic food sector, if food security in Indonesia is to be secure in the face of global economic uncertainty that unsettles everything.